Size-dependent deflection of cross-ply composite laminated plate induced by piezoelectric actuators based on a re-modified couple stress theory - Wang, H.; Li, Z.; Zheng, S. (Archives of Mechanics, 2019)
A size-dependent model for cross-ply composite laminated plate bonded with PZT actuators is developed by using re-modified couple stress theory (RMCST), which only uses two material length scale parameters to describe the size-dependent effect. An equivalent bending moment model and a refined model are developed by using two different ways. The analytical solution of equivalent bending moment model for simply supported composite laminated plate is obtained. The equilibrium equation of motion and corresponding boundary constraints of the refined model are established from the potential energy principle. The Ritz approximate solution of transverse deflection of the refined model indicates that the size-effect cannot be ignored in micro-scale. Numerical examples are given to account for the effect of material length scale parameters and dimensions of piezoelectric actuators on the defection of composite laminated plate.